Finite Element Analysis of Wood Structural Joints on Traditional Wooden Ship - , Yohanes; Akbar, Musthafa; Aksa, Reysca Admi (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2016)
Traditional ship often made by woods materials and it was made without proper engineering procedure. This research focuses on a case study in BaganSiapiapi, Riau Province, Indonesia where a large wooden ship was manufactured. One of the sources of material failure in the manufacturing of wooden ship is located at the joint. In this research, a modification of joint design has been studied where 4 design model have been offered by using glue as the attachment materials and 5 other design by using bolt as the connection method. A finite element method was used to study the strength of the joint which has been guided by a standard issued by Indonesian Classification Bureau. There are 9 design of joints were modeled and studied which have been varied using two different wooden materials such as ‘keruing’ and ‘meranti’. A uniform loading was applied on all models and materials. The applied loadings are buoyancy force, gravity force, and pre-stress loading at the bolt. The result from simulation generates a stress-contour indicating the stress level on the materials. It was concluded that the model of connection hooked straight lip which is connected with 4 pieces M14 bolts with wood material keruing a recommended model for traditional wooden boat building. This design gives 1.605 mm deformation with maximum stress of 217.51 MPa.